The effects of football programmes on the transformation of anthropological characteristics of young football players - Bajric, O.; Selimovic, N.; Bajric, S.; Srdic, V. (Sport Science - International Scientific Journal of Kinesiology, 2015)
The research was conducted on the sample group of 137 football players, ages from 14 to 16, from football clubs in the area of Central Bosnia Canton. 9 variables for assessment of morphological characteristics, 15 variables for the assessment of motor skills and 12 variables for the assessment of situational motoric skills were conducted. The main objective of this research was to determine the effects of experimental football programs over a period of six months with 72 training units on the transformation of morphological characteristics, motor skills and situational motor skills of young players. The canonical discriminant analysis was conducted with the aim of establishing the effects of the experimental program on the transformation of morphological characteristics, motor skills and situational motor skills of young players. The general quantitative changes that developed within certain variables of the motoric skills and situational motoric behavior are the result of a significant increase in efficiency of a number of physical abilities, especially during the period of the experimental football program.